Treatment of refractory hematospermia with Finasteride: A prospective placebo-controlled study (Bangladesh Journal of Urology, 2023)
Background: Finasteride is being used to treat recurrent hematuria due to BPH. Androgen has an essential role in the production of angiogenic factors such as VEGF. Vessel density & VEGF decreases after finasteride treatment and thus improve haematospermia.Objective: To test the efficacy of finasteride to control refractory idiopathic hematospermia for which conservative treatment has failed.Methodology: This Prospective placebo-controlled study was carried out from July 2019 to June 2022 with 48 patients of hematospermia presented to the outpatient department of NIKDU. Twenty-two patients had refractory hematospermia of idiopathic nature. They were randomized into two equal groups, 11 patients in each group. One group received 5 mg finasteride daily for 3 months, and the other group received placebo. Patients were followed up with semen analysis and TRUS for 3 consecutive months and after 1 year.Result: In the finasteride-treated group, remission of hematospermia occurred in 5 patients (45%) within 1 month. Patients continued treatment for 3 months without the recurrence of hematospermia. After stopping finasteride treatment, hematospermia recurred in 3 out of 9 patients 12 months later. Two cases were not improved, but a significant decrease in frequency & amount of bleeding was observed in semen analysis. In the placebo-treated group, cessation of hematospermia occurred in 3 cases (27%) versus 9 (81%) in the finasteride group (P = 0.03) after 3 months of treatment.Conclusion: Three months of treatment with finasteride for refractory idiopathic hematospermia significantly cures hematospermia with no undesirable side effects.Bangladesh J. Urol. 2022; 25(1): 33-66